Hydraulic characteristics of capillary wick irrigation system - Muhammed, Hadi Hamaaziz; Kamal, Md. Rowshon (2015)
Limited availability of freshwater supply worldwide demonstrates urgent need to develop and adopt efficient irrigation methods and effective irrigation management strategies. This study, by conducting laboratory experiments, investigated hydraulic characteristics and performance of cotton-bonded non-woven material to be used as wick emitter. The wick emitter provided uniformity coefficient of 95.65% and distribution uniformity of 92.67% in applying irrigation in two growing media - peatgro (peat) and coconut coir dust. The growing media were wetted in an axially symmetric pattern under the wick emitter; in traditional and modern watering methods, growing media are wetted in one-dimensional pattern. HYDRUS simulation of water distribution revealed dependency of spatial extent of the wetted zone in the growing media on water application period and hydraulic properties of the media. Discharge of the wick emitter followed an inverse linear relation with capillary height of water in the wick. This relation lead to development of an equation for compensating wick emitter discharge by replacing pressure head of drip emitter with capillary height in wick emitter. The findings of this study thus invoke opportunities to develop an effective Capillary Wick Irrigation System (CWS). Further investigation would provide a generalized broader evidence on CWS performance based on techno-economical performance of the wick under diverse conditions.